2018
DOI: 10.1093/schbul/sby153
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Ideation in People With Psychosis Not Taking Antipsychotic Medication: Do Negative Appraisals and Negative Metacognitive Beliefs Mediate the Effect of Symptoms?

Abstract: Between 5% and 10% of people with psychosis will die by suicide, a rate which is 20-75 times higher than the general population. This risk is even greater in those not taking antipsychotic medication. We examined whether negative appraisals of psychotic experiences and negative metacognitive beliefs about losing mental control mediated a relationship between psychotic symptoms and suicidal ideation in this group. Participants were diagnosed with schizophrenia spectrum disorders, antipsychotic-free for 6 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Therefore, findings of the present study must be considered as preliminary and replicated in independent samples, including healthy controls as well as other clinical populations with different levels of structural integration. Future clinical studies might include comparisons between psychodynamic and synthetic metacognitive approaches in terms of specific interventions, as well as multi-method designs, relative vs. absolute measures of psychosocial functioning and further relevant outcome measures like suicidality (Hutton et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, findings of the present study must be considered as preliminary and replicated in independent samples, including healthy controls as well as other clinical populations with different levels of structural integration. Future clinical studies might include comparisons between psychodynamic and synthetic metacognitive approaches in terms of specific interventions, as well as multi-method designs, relative vs. absolute measures of psychosocial functioning and further relevant outcome measures like suicidality (Hutton et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) and Pyle, Stewart, et al (2015) found that baseline scores on the ‘negative appraisals of experience’ and ‘expectations’ subscales were predictive of depression at 3‐ and 6‐month follow‐up, respectively. Three studies investigated the association between negative beliefs and suicidal ideation or risk over periods between 6 and 18 months, but no significant relationships were reported (Hutton et al , 2019; Pyle, Stewart, et al , 2015; Stip, et al , 2017). However, small samples in two of these studies likely limited power ( n = 45–68).…”
Section: Resultsmentioning
confidence: 99%
“…A small number of studies controlled for psychosis symptoms (Birchwood et al , 2007; Hutton et al , 2019; Karatzias, Gumley, Power, & O’Grady, 2007; Rooke & Birchwood, 1998; Shahar, Weinberg, McGlashan, & Davidson, 2010; Upthegrove et al , 2014). These publications reported that when controlling for psychosis symptoms, cognitive appraisals (e.g., entrapment, loss) remained significantly associated with depression, anxiety, and (in one study; cross‐sectional association in Hutton et al, 2019) suicidal ideation, whilst psychosis symptoms (e.g., positive symptoms) were not found to significantly predict emotional distress.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paul Lysaker et al 11 demonstrate the link between meta-cognition and disturbances in awareness of illness regardless of any accompanying symptom configuration, and Kelsey Bonfils et al 12 present novel findings linking metacognition with empathy, one of the foundations of human relatedness; these 2 articles rely on Paul Lysaker's approach. Finally, Paul Hutton et al 13 build upon Wells' model and describe how both negative appraisals of psychotic experiences and negative metacognitive beliefs about worry may mediate the relationship between psychotic symptoms and suicidal ideation.…”
mentioning
confidence: 99%